Aneustat (OMN54) has aerobic glycolysis‐inhibitory activity and also immunomodulatory activity as indicated by a first‐generation PDX prostate cancer model. Issue 2 (1st March 2018) - Qu, Sifeng; Xue, Hui; Dong, Xin; Lin, Dong; Wu, Rebecca; Nabavi, Noushin; Collins, Colin C.; Gleave, Martin E.; Gout, Peter W.; Wang, Yuzhuo
Abstract : Aneustat (OMN54) is a multivalent, botanical anticancer candidate therapeutic. A recent Phase‐I clinical trial has indicated that it is well tolerated by patients and has immunomodulatory activity. In our study, using in vitro and in vivo prostate cancer models, we investigated Aneustat with regard to effects on (i) cancer‐generated immunosuppression based on aerobic glycolysis leading to acidification of the tumor microenvironment, and (ii) immune‐related processes such as macrophage differentiation and shifts in the intratumoral levels of host immune cells. Aneustat markedly reduced glucose consumption, lactic acid secretion, glycolysis‐related gene expressions and proliferation of human LNCaP prostate cancer cells. In addition, Aneustat induced differentiation of RAW264.7 macrophages to the M1 anticancer phenotype. Treatment of LNCaP xenografts and first‐generation patient‐derived prostate cancer tissue xenografts with Aneustat in both cases led to a marked shift in intratumoral host (mouse/patient) immune cell levels: a higher ratio of cytotoxic CD8 + T/Treg cells, higher numbers of NK cells, lower numbers of Treg cells and MDSCs, i.e. changes favoring the host anticancer immune response. Taken together, the data indicate that Aneustat has immunomodulatory activity based on inhibition of aerobic glycolysis which in patients may lead to reduction of cancer‐induced immunosuppression. Furthermore, first‐generation patient‐derived cancer tissue xenograft models may be used for screening compounds for immunomodulatory activity. Abstract : What's new? Aneustat is a first‐in‐class multivalent, botanical immuno‐oncology candidate therapeutic; as indicated by a recent Phase‐I trial, it is well‐tolerated by patients. But the mechanisms of action underlying its immunomodulatory activity remain unclear. Using a first‐generation patient‐derived prostate cancer tissue xenograft model, the authors found that treatment with Aneustat induced a shift in the levels of intra‐tumoral patient immune cells, favoring the host anticancer immune response considered critical for cancer treatment. This immunomodulatory activity appears to be based on inhibition of aerobic glycolysis resulting in reduced acidification of the tumor microenvironment, which in patients may lead to reduction of cancer‐induced immunosuppression.